2017
DOI: 10.1080/08874417.2017.1300514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perceived Risk on Intention to Purchase: A Meta-Analysis

Abstract: This article conducts a meta-analysis to determine the effect of perceived risk on intention to purchase in e-commerce settings. The literature generally favors the negative relationship between the two variables; however, some studies have found this relationship to be not significant or even positive. Thirty-five studies were examined, representing 39 overall samples across multiple contexts with a total sample size of 13779 and overall weighted effect size (Pearson's r) for all studies of −0.362 (95% CI: −.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 52 publications
2
65
0
8
Order By: Relevance
“…Y. Chen & Teng, 2013;Fortes & Rita, 2016;S. Ha & Stoel, 2009;Pelaez et al, 2019) of online shopping systems positively affect users' attitudes toward such systems. Numerous studies also showed that PEOU of online shopping systems positively affects PU of such systems (Agag & El-Masry, 2016;Bigné-Alcaniz et al, 2008;Fortes & Rita, 2016;S.…”
Section: Perceived Ease Of Use (Peou) and Perceived Usefulness (Pu)mentioning
confidence: 99%
“…Y. Chen & Teng, 2013;Fortes & Rita, 2016;S. Ha & Stoel, 2009;Pelaez et al, 2019) of online shopping systems positively affect users' attitudes toward such systems. Numerous studies also showed that PEOU of online shopping systems positively affects PU of such systems (Agag & El-Masry, 2016;Bigné-Alcaniz et al, 2008;Fortes & Rita, 2016;S.…”
Section: Perceived Ease Of Use (Peou) and Perceived Usefulness (Pu)mentioning
confidence: 99%
“…The academic fraternity has always given less attention to behaviour deterrents (Rehman et al, 2020) and focus primarily being on the drivers (Farivar et al, 2017). Therefore, given the importance of risk in e-commerce (Pelaez et al, 2019;Samhan, 2018), perceived risk (PR) has been added to the UTAUT2 model. Also, Dwivedi et al (2019) found that the addition of attitude to the original UTAUT model would increase its predictive power.…”
Section: Introductionmentioning
confidence: 99%
“…Online shopping behaviour of consumers started to be analysed at the beginning of the 1990s. The impact of perceived risk on shopping attitudes has been examined in an increasing number of empirical studies (Pelaez, Chen, Ch-W. & Chen, Y.X., 2017;Iconaru, Perju & Maconvei, 2012). The work of Forsythe and Shi (2003) must be mentioned in connection to this.…”
Section: Theoretical Backgroundmentioning
confidence: 99%